Experimental and numerical study of stainless steel channel-to-gusset plate connections - Jiang, Ke (2022)
With the advantages offered by stainless steel in terms of sustainability, mechanical performance and superior serviceability, structural application of stainless steel is prevalent. This paper presents experimental and numerical studies of stainless steel channel-to-gusset plate connections failing by net section fracture. The experimental programme was carried out on 16 stainless steel channel-to-gusset plate connections, with each consisting of a channel section member bolted to two gusset plates by web or flange. The test setup and procedures as well as the key test results, including the failure loads, load–elongation curves, failure modes and strain distribution at critical cross-sections, were reported in detail. The effects of connection length, out-of-plane eccentricity and in-plane eccentricity on net section efficiency were discussed. Following the experimental programme, a numerical modelling programme was performed, where finite element models were firstly developed to replicate the tests and then employed to conduct parametric studies to generate further numerical data over a wide range of cross-section dimensions and connection lengths. Based on the test and numerical data, the existing design rules for stainless steel channel-to-gusset plate connections failing by net section fracture, as given in the European code and American specification, were evaluated. Generally, the European code yields excessively conservative and scattered failure load predictions, while the American specification leads to unsafe and scattered failure load predictions. An improved design approach was proposed and shown to provide substantially improved failure load predictions over the design codes.